Severe gynecomastia due to anti androgens intake: A case report and literature review - Chentli Farida; Belhimer Faiza (Indian Journal of Endocrinology and Metabolism, 2013)
Gynecomastia is the most bothersome side effect in men taking antiandrogens. It is exceptionally severe and distressing physically and mentally as in the reported case. A man, aged 63, with a history of a well-treated macroprolactinoma, was referred in 2004 for gynecomastia that appeared after treatment by microsurgery, radiotherapy and flutamide for a lesion suspected to be prostate cancer. Clinical examination was normal except for huge enlargement of the breasts. Mammography and breasts MRI did not show any tumor. There was not any metastasis of the supposed prostate cancer and prostatic acid phosphates were within normal ranges. Hormonal exploration showed subclinical hypogonadism [testosterone: 7.4 ng/ml (n: 3-9), FSH: 14.9 mu/ml (n: 0.7-11) and LH: 9.7 mu/ml (n: 0.8-7.6)]. Testes ultrasounds were normal. Radiological and hormonal adrenal explorations were normal [Cortisol: 76 ng/ml (n: 50-250), DHEA-S: 59 μg/ml (n: 50-560), E2:40.2 pg/ml (n < 50)]. Body scan was normal too. The discussed etiologies were post radiation subclinical hypogonadism, and treatment with anti androgens. After flutamide withdraw, there was not any sign of prostate cancer recurrence, and gynecomastia decreased significantly, but did not disappear probably because of fibrosis.